Aktivasi Oosit Menggunakan Strontium Klorida setelah Injeksi dengan Spermatozoa Domba Hasil Pengeringbekuan (OOCYTE ACTIVATION USING STRONTIUM CHLORIDE FOLLOWING INJECTION OF FREEZE-DRIED RAM SPERMATOZOA) - Saili, Takdir; Djuwita, Ita; Setiadi, Mohamad Agus; Agungpriyono, Srihadi; Boediono, Arief (Jurnal Veteriner, 2013)
One of the factors that inhibit the formation of male pronuclei following injection of freeze-dried ramspermatozoa was the absence of artificial activation during oocyte incubation after the injection. Therefore,in this experiment the ability of strontium chloride (SrCl2) to improve oocyte activation followingintracytoplasmic sperm injection (ICSI) was evaluated. Aceto lacmoid staining was used to assessdecondensation and pronucleus formation following ICSI. Results of this experiment revealed that freezedriedspermatozoa had the ability to decondense and to form 1PN following injection into oocytes evenwithout artificial activation, but failed to form 2PN. However, 40% of 2PN oocytes were obtained when theinjected oocytes was first incubated for 20 minutes in medium containing 50 mM strontium chloride thensubsequently incubated for 10 hours in medium without strontium. On the contrary, the 2PN oocytes werenot observed either in injected oocyte neither without artificial activation nor in non-injected oocytes withartificial activation. In conclusion, freeze-dried ram spermatozoa were able to decondense and to support2PN formation following ICSI and artificial activation using strontium.
Keywords: freeze-drying, spermatozoa, ICSI, activation, pronucleus, strontium